The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/jme/tjab067
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Behavior and Species Diversity of the Anopheles barbirostris Complex (Diptera: Culicidae) in Thailand

Abstract: Species of the Anopheles barbirostris complex (Myzorhynchus Series of the subgenus Anopheles) are potential vectors of malaria and filariasis parasites. Owing to the lack of reliable identification methods, the biting activity and host preference of the species within this complex have not been previous described. In this study, the trophic behavior and host preferences of the species in the complex were determined in Thailand, and a map of their geographical distributions constructed. Adult female mosquitoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…AS-PCR used species-specific differences within the sequences of the internal transcribed spacer 2 (ITS2), a ribosomal DNA gene (rDNA) widely used to differentiate cryptic species of Asian Anopheles complexes [ 44 ] and reliably identified five species in the Barbirostris Complex in Thailand [ 73 ]. Another recent study by Udom et al [ 74 ] on the same group included PCR-identified Pu Teuy specimens and provided a national map of Anopheles species complex distribution. From these genetic studies in Pu Teuy, correct species identification is essential and mandatory for basic and applied mosquito studies and for the evaluation of vector control strategies [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…AS-PCR used species-specific differences within the sequences of the internal transcribed spacer 2 (ITS2), a ribosomal DNA gene (rDNA) widely used to differentiate cryptic species of Asian Anopheles complexes [ 44 ] and reliably identified five species in the Barbirostris Complex in Thailand [ 73 ]. Another recent study by Udom et al [ 74 ] on the same group included PCR-identified Pu Teuy specimens and provided a national map of Anopheles species complex distribution. From these genetic studies in Pu Teuy, correct species identification is essential and mandatory for basic and applied mosquito studies and for the evaluation of vector control strategies [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing PQ without G6PD testing has been reported to cause hemolysis in P. vivax infected patients, particularly at risk for the individuals with low G6PD enzyme activity. Even with the correct dose, intravascular hemolysis in male with G6PD Mahidol variant can occur [50]. It has been demonstrated that the G6PD Viangchan and Mahidol, the most common variants observed in southern Thailand, cause low enzymatic activity in RBCs and risk for acute hemolysis induced by PQ [51,52].…”
Section: Discussionmentioning
confidence: 99%